Effects of Goal-Framed Messages on Mental Health Education Among Medical University Students: Moderating Role of Personal Involvement - Bai, Li; Rao, Qingmao; Cai, Zhengjie; Lv, Yalan; Wu, Tingting; Shi, Zumin; Sharma, Manoj; Zhao, Yong; Hou, Xiaorong (Frontiers in Public Health, 2019)
Mental health problem among university students is an emerging public health issue, and mental health education has always been the focus of attention for universities. However, limited attention has been paid to the effect of students' acceptance of health messages. Previous studies have found that message framing plays a key role in the process of responding to health-promoting messages. In this backdrop, the study aimed to examine the effects of goal-framed messages on mental health education among medical university students and investigate the moderating role of personal involvement. A cross-sectional study was conducted on medical university students. An online self-administered questionnaire was used to collect data. Wilcoxon rank-sum test and ordinal logistic regression were used for data analysis. Results showed significant differences in message acceptance between the gain- and loss-framed groups (p < 0.001). Participants with high personal involvement had higher message acceptance than those with low personal involvement in gain- and loss-framed message models (p < 0.05). Specifically, participants who related to roommates with high intimacy had higher message acceptance than those who related to roommates generally (p < 0.05). Participants who were concerned about their health condition had higher message acceptance than those who were neutral about their health condition (p < 0.001). Evidence of advantages of gain- over loss-framed messages on mental health among medical university students was found. The hypothesis that personal involvement with a health issue affects the acceptance of message framing was supported. Public health advocates can use framed message as a strategy to improve the efficacy of intervention in mental health education.